Pengaruh Penambahan Graphene Oxide Terhadap Sifat Bioplastik Berbasis Pati Singkong - Ekawati, Lestari; Amri, Amun; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Conventional plastics are still often used today derived from synthetic polymer materials that are difficult to be recycled and degraded by microorganisms. Bioplastic is one of solution to this problem. One of the materials that have the potential to be used as raw material is cassava because it has a high starch content. However, starch has a weakness that is still low mechanical properties. The general purpose of this research is to study the effect of adding graphene oxide and stirring time to mechanical properties, and biodegradation of cassava starch based bioplastic. Bioplastic was synthesized by intercalation method with variation of graphene oxide concentration (5% v / v and 15% v / v) and stirring time variation (30 minute and 60 minute). The results of the analysis showed that the treatment with the addition of filler graphene oxide and the variation of stirring time contributed to the resulting bioplastic mechanical properties. Bioplastic with the best characteristic was obtained by adding 15% graphene oxide and 60 minutes stirring time with tensile strength 3,92 Mpa, elongation 13,216%, modulus young 29,66 Mpa with water resistance 27,42% and within 1 week degraded 50 , 83%.Keywords: Bioplastic, glycerol, graphene oxide, Cassava Starch, plasticizer